2007
DOI: 10.1007/s10459-007-9088-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors that predict clinical performance in medical school

Abstract: Academic achievement indices including GPAs and MCAT scores are used to predict the spectrum of medical student academic performance types. However, use of these measures ignores two changes influencing medical school admissions: student diversity and affirmative action, and an increased focus on communication skills. To determine if GPA and MCAT predict performance in medical school consistently across students, and whether either predicts clinical performance in clerkships. A path model was developed to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…White et al showed that MCAT scores did not predict the performance of minority students in the first year of medical school but did predict performance of majority students. 33 Additionally, Davis et al's comprehensive review of the MCAT showed that black examinees had lower average MCAT scores than white examinees. 34 This mirrored differences on other admissions standardized tests.…”
Section: Discussionmentioning
confidence: 99%
“…White et al showed that MCAT scores did not predict the performance of minority students in the first year of medical school but did predict performance of majority students. 33 Additionally, Davis et al's comprehensive review of the MCAT showed that black examinees had lower average MCAT scores than white examinees. 34 This mirrored differences on other admissions standardized tests.…”
Section: Discussionmentioning
confidence: 99%
“…There are also many research results indicating a need for transparent and effective admission systems, as well as tools for assessing the non-cognitive abilities that may be significant in the medical career (McManus et al 2005;Cave et al 2007;Bore et al 2009;Fernando et al 2009;Powis 2009;O'Neill et al 2009;White et al 2009). …”
Section: Practice Pointsmentioning
confidence: 99%
“…Additionally, specific attributes of the student, evaluator, or environment in which the interaction took place might affect the student's scores by introducing systematic differences into the measurement, further decreasing the reliability of the system. While previous research has studied the relationships between various demographic data of those being evaluated and their numerical scores 1,[3][4][5][6][7][8][9][10][11] as well as the reliability of clinical Correspondence: Ryan Spielvogel, 4860 Y Street, Suite 1600, Sacramento, CA 95817, USA Email: Ryan.Spielvogel@gmail.com evaluations, 4 few have investigated the effect these have on the system's overall reliability or further explored the specific sources of the variation. Additionally, many studies on this topic examined evaluations of residents by faculty.…”
Section: Introductionmentioning
confidence: 99%